EFEKTIVITAS PEMBERIAN AROMA TERAPI LAVENDER TERHADAP PENGURANGAN MUAL MUNTAH PADA IBU HAMIL TRIMESTER 1 : pengaruh pemberian aroma terapi lavender - Erni Hernawati Sutisna (Jurnal Asuhan Ibu dan Anak, 2022)
Abstract Excessive nausea and vomiting that occurs in pregnant women can cause electrolyte imbalances, weight loss, dehydration, ketosis, and nutritional deficiencies. This study aims to analyze the effectiveness of giving lavender aromatherapy to reduce nausea and vomiting in first trimester pregnant women. The analysis used in this research is dependent and independent sample t-test. The results of this study showed a significant decrease in nausea and vomiting in the intervention group after giving lavender aromatherapy as evidenced by the T test, p value = 0.000 (p value <0.05). Keywords: aromatherapy, pregnant women, nausea and vomiting